Evaluation of Trinexapac‐Ethyl and Nitrogen Management to Minimize Lodging in Rice. (1st November 2016) - Corbin, Jennifer L.; Walker, Timothy W.; Orlowski, John M.; Krutz, L. Jason; Gore, Jeffrey; Cox, Michael S.; Golden, Bobby R.
Abstract : Rice ( Oryza sativa L.) is an important crop in the midsouthern United States. However, some high‐yielding cultivars are highly susceptible to lodging. The plant growth regulator, trinexapac‐ethyl (TE), has been shown to decrease lodging in upland cereal crops, but data are scarce that demonstrate rice response to TE. The objective of this study was to determine the effect of TE on rice plant height, lodging, and grain yield. Experiments were established at multiple locations during the 2012 and 2013 growing seasons in Mississippi. Trinexapac‐ethyl was applied to a lodging‐susceptible rice cultivar at 12, 24, and 48 g a.i. ha −1 at two timings: panicle differentiation (R1) and R1 + 14 d. Rice response to TE was determined for rice that received 100% of N applied at V3 and rice that received a two‐way split N strategy (75% N at V3 and 25% at R1). On both clay and silt‐loam soils all rates of TE reduced plant height and lodging compared to nontreated rice. The effect of TE on rice grain yield was variable. On silt‐loam soils 12 g a.i. ha −1 TE resulted in rice grain yield similar to nontreated rice when applied at R1, but decreased grain yield when applied to rice at R1+ 14 d. The 48 kg a.i. ha −1 rate decreased rice grain yield on both soil textures. The results of this study indicate that trinexapac‐ethyl may be a useful tool to manage lodging, but further research is needed refine TE use guidelines in rice. Trinexapac‐ethyl decreased rice plant height and lodging on both clay and silt loam soils. Trinexapac‐ethyl at 12 g a.i. ha −1 did not decrease grain yield when applied at panicle differentiation on silt loam soils. Grain yield response to trinexapac‐ethyl varied by soil texture and N management strategy.